2
$\begingroup$

Assume we have a model of OVG where there are 2 overlapping generations, youngs and olds, the agents are two period living. The utility function is logaritmic, and the production function is Cobb-Douglas.

I have to show that the solution for the social planner does not coincide with the equilibrium from the market. The social planner solves: $$\max \ln(c_t^y)+\beta \ln(c_{t}^o)$$ $$s.t.$$ $$c_t^y+\frac{c_t^o}{1+n}+k_{t+1}(1+n)-k_t=f(k_t)$$ Where the units are expressed in per capita terms and $n$ represents the population growth rate. The FOC for the social planner is $$\frac{c_{t}^o}{c_t^y}=\beta(1+n)$$ We know that in steady state the level of consumption is actually constant i.e. $c_t^o=c^o$ and $c^y_t=c^y$. What I am not getting is if I should replace this on the constraint in order to obtain the values of S.S. or if I need to take the FOC with respect to the $k$. I am a little bit lost, since I've already solved the problem for the market economy but I am having a hard time figuring out how to proceed. Any hint will be greatly appreciated.

$\endgroup$
  • $\begingroup$ The problem is that you are choosing three variables, not two, (plus the multiplier) i.e. you must choose $C_t^y,C_t^o,$ and $k_{t+1}$ (and of course for $\lambda_t$). This will give you four first-order conditions rather than 3. Eliminate $\lambda$ from the system and then impose steady state. See my solution below. $\endgroup$ – dlnB Mar 15 at 18:27
1
$\begingroup$

Start by writing the Lagrangian (as it sounds like you have already done):

$$L=\sum_{t=0}^{\infty} \{\beta^t(\ln C_t^y + \ln C_t^o) + \lambda_t (C_t^y +\frac{C_t^o}{1+n} +k_{t+1}(n+1)-k_t-f(k_t))\}.$$

First order conditions are given by $$\frac{\partial L}{\partial C_t^y} = \frac{\beta^t}{C_t^y} +\lambda_t = 0$$ $$\frac{\partial L}{\partial C_t^o} = \frac{\beta^t}{C_t^o} +\frac{\lambda_t}{1+n} = 0$$ $$\frac{\partial L}{\partial k_{t+1}} = \lambda_{t-1}(1+n) - \lambda_t(1 + f'(k_t)) = 0$$ $$\frac{\partial L}{\partial \lambda_{t}} = C_t^y +\frac{C_t^o}{1+n} +k_{t+1}(n+1)-k_t-f(k_t)=0.$$

First notice the first two equations give us $$\frac{C_t^y}{C_t^o} = 1+n.$$ Also notice that the first equation implies $\lambda_t = -\frac{\beta^t}{C_t^y}$. Substituting this into our third equation gives $$\frac{\beta^{t+1}}{C_{t+1}^y}(1+n) = \frac{\beta^{t}}{C_{t}^y}(1+n)(1 + f'(k_t)$$ or equivalently $$\frac{\beta C_t^n}{C_{t+1}^y} = (1 + f'(k_t)).$$

Finally, we can write our system of four equations with three equations, having removed $\lambda$ from the system: $$\frac{C_t^y}{C_t^o} = 1+n$$ $$\frac{\beta C_t^y}{C_{t+1}^y} = (1 + f'(k_t)).$$ $$C_t^y +\frac{C_t^o}{1+n} +k_{t+1}(n+1)-k_t-f(k_t)=0.$$

Dropping time subscripts, i.e. applying the steady-state condition, gives $$\frac{C^y}{C^o} = 1+n$$ $$\beta = (1 + f'(k)).$$ $$C^y +\frac{C^o}{1+n} +nk-f(k)=0.$$

Hence, you are left with a system of three equations with three unknowns $C^y$, $C^o$, and $k$. Solve the system to arrived at a steady-state solution.

$\endgroup$
  • $\begingroup$ Very clear! Thanks for the answer, it was very helpful $\endgroup$ – RScrlli Mar 15 at 21:14
  • $\begingroup$ Good luck with your PhD studies (or very advanced undergraduate studies)! $\endgroup$ – dlnB Mar 15 at 21:15

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.